Analisis Efektivitas dan Potensi Pajak Reklame Sebagai Sumber Pendapatan Asli Daerah Kota Bitung Tahun 2015–2019 : Penelitian - Gebriany Pirade Wenur (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The implementation of regional autonomy, focusing on the role of district and city governments, begins with the delegation of authority from the central government to local governments. This decentralization process requires strengthening in local financial management. Local Revenue (PAD) is one of the main sources of regional funding that can be independently utilized to support governance and development. In Bitung City, local taxes play an important role in local revenue (PAD), with significant contributions and promising revenue potential. Optimizing advertising collection, both in terms of effectiveness and potential management, is a strategic step to increase PAD. This study aims to analyze the effectiveness level and potential of advertising tax revenues for PAD in Bitung City using a descriptive quantitative method at the Regional Tax and Retribution Management Agency (BP2RD).The results indicate that advertising tax collection in 2015–2018 was highly effective, with achievements above 100% (104.60% in 2015; 150.71% in 2016; 115.01% in 2017; and 101.39% in 2018). In 2019, effectiveness decreased to 93.72% but remained in the effective category. The potential advertising tax revenue that BP2RD could optimize in 2020 was estimated at IDR 147,966,302,879.